Is Maqāṣīd al-Sharī’a Sufficient? Reflections on Islam in Contemporary Malaysia - Ahmad Fauzi Abdul Hamid (Universitas Islam Negeri Mataram, 2020)
During its brief 22-month administration (May 2018 – February 2020), Malaysia’s Pakatan Harapan government put forward the idea of Maqāṣīd al-Sharī’a or higher objectives of Islamic law as one of the precepts governing its Islamic agenda. While such an approach has demonstrated streaks of viability in extricating Islam from overly legalistic mores, it is epistemologically undetached from the sharia-centric paradigm that has dominated the post-colonial Muslim intellectual make-up. This article argues that proponents of Maqāṣīd al-Sharī’a in Malaysia might have overlooked the more urgent need for a morally based framework that evaluates human action not on the extent to which humans observe external law but rather on how sensitively humans connect with God in the event of legal injunctions being adhered to, ignored or transgressed. What is needed in Malaysia in addition to Maqāṣīd al-Sharī’a is Maqāṣīd al-Akhlāq, whose origins are rooted in the Islamic spiritual tradition of taṣawwuf or sufism.